Gestire il cambiamento: Renzi, il PD e il nuovo “collateralismo” - Sampugnaro, Rossana (SocietàMutamentoPolitica, 2017)
The organization patterns of the parties depend on new needs and on segmentation of interests. Political participation is very instable and develops often outside the traditional political organizations and in individualized manner on the web. In many parties, the reaction is the de-differentiation and the de-burocratization, linked to total or partial outsourcing of some functions: funding, interests aggregation, political mobilization, study of new policies or management of communication. For these goals, we observe the activities of organizations (think tanks, foundations, electoral committees), often directly dependent from the leader of party. The study proposes this approach to know the recent transformations in Partito Democratico after the “primary election” of Renzi as party leader: the contraction of party organization, the strong personalization of the leadership and the birth of new personal organizations as Leopolda and FutureDem. These new organizations are fundamental elements of “Renzi’s method” to make funding, to mobilize new supporters (often very different from traditional Pd membership), to elaborate and construct new policies and especially to include heterogeneous groups and single person, not always compatible with the party and its traditional rituals. From supporters’ recruitment point of view, this is very important for party. Thanks to a web survey, the study explore profiles of two organization for young people: “Giovani democratici” the youth branch of PD and FutureDem, a youth organization linked directly to leader. The presence of very different profiles is a resource for mobilization but it could became a critical element to construct shared public policies.